Addressing and Inspiring Vaccine Confidence in Black, Indigenous, and People of Color During the Coronavirus Disease 2019 Pandemic. (9th August 2021) - Marcelin, Jasmine R; Swartz, Talia H; Bernice, Fidelia; Berthaud, Vladimir; Christian, Robbie; da Costa, Christopher; Fadul, Nada; Floris-Moore, Michelle; Hlatshwayo, Matifadza; Johansson, Patrik; Kullar, Ravina; Manning, Kimberly; et al.
Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, we have witnessed profound health inequities suffered by Black, Indigenous, and People of Color (BIPOC). These manifested as differential access to testing early in the pandemic, rates of severe disease and death 2–3 times higher than white Americans, and, now, significantly lower vaccine uptake compared with their share of the population affected by COVID-19. This article explores the impact of these COVID-19 inequities (and the underlying cause, structural racism) on vaccine acceptance in BIPOC populations, ways to establish trustworthiness of healthcare institutions, increase vaccine access for BIPOC communities, and inspire confidence in COVID-19 vaccines.